PENGARUH STRATEGI BISNIS, TRANSFER PRICING, DAN KONEKSI POLITIK TERHADAP TAX AVOIDANCE (Studi pada Perusahaan di Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2016-2018) - Nurrahmi, Alya Dinda; Rahayu, Sri (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This study aims to analyze the influence of business strategy factors, transfer pricing, and political connections on tax avoidance in companies in the mining sector listed on the Indonesia Stock Exchange (BEI) in 2016-2018. The data analysis technique is panel data regression analysis using EViews 10. The population in this study is companies in the mining sector listed on the IDX. The sampling technique used was purposive sampling and produced 21 samples with the study period in 2016-2018 so there were 63 sample units. The results showed that simultaneous business strategy, transfer pricing, and political connections significantly influence tax avoidance. While partially business strategy has no effect on tax avoidance, transfer pricing has a positive effect on tax avoidance, and political connections have a negative effect on tax avoidance.